Controversies in guidelines for teacher training and their contradictions with field education (Revista Contexto & Educação, 2025)
The elaboration is part of the reflections on training of educators in the field and aims to analyze the guidelines of teacher training (s) considered the documents in force between the years 2015 and 2024 and that have regulated teacher training in the last decade in Brazil. Some controversies present in the guidelines of this formation are highlighted with notes on their contradictions with the fight for a Field Education. Resolution CNE/CP n° 2/2015, Resolution CNE/CP n° 2/2019 were considered to replace the previous document and the current version, circumscribed in Resolution CNE/CP n° 4/2024. Being sustained in the bibliographic and documentary research, from the analysis of the referenced resolutions, proximities and differences between them are addressed, with the Field Education as a counterpoint to neoliberal and conservative logic driven by the incidence and interference of business reformers in Brazilian education, with particular emphasis on its activity in the preparation of the guidance documents for teacher training in the country. Controversies are recorded about the guidelines for training teachers and their possible implications in the formation of those professionals participes of formative processes focused on the activity in the Field Education, which, in turn, points to accounts of the formulations placed in the documents with the concreteness of the Field Education in its source materiality.
Keywords: Guidelines for Teacher Training; Field Education; Business Reformers